Hepatic Peliosis and Hemorrhage after Anabolic Steroid Abuse - Kausthubh Hegde; Patrick D. Sutphin; Thomas J. An; Sanjeeva P. Kalva
Anabolic steroid abuse has become prevalent in modern society, with many athletes and bodybuilders using these substances for their performance-enhancing effects. A significant concern related to anabolic steroid abuse is the potential development of androgen-associated liver tumors such as hepatocellular carcinoma and adenomas. Anabolic steroid abuse has also been associated with hepatic vascular abnormalities like hepatic peliosis, a rare condition characterized by blood-filled cavities within the liver parenchyma. Hepatic peliosis can present with nonspecific symptoms or remain asymptomatic, making it difficult to diagnose without appropriate imaging studies. In this case report, the authors describe the imaging findings and management of two patients with intrahepatic bleeding associated with anabolic steroid consumption.